Cultivating communities of practice: the CGIAR information management professionals' experience - Ramos, M.M.; Soeripto, S.W.; Ali, M.K. (2003)
A community of practice (CoP) is defined as a group who share a common concern or a commitment towards a goal, and find solutions to common problems. Successful collaboration through CoPs is well documented in current literature. Presently, information providers face bigger challenges in servicing the requirements of end-users and stakeholders. Information and communication technologies (ICT) altered the format, quantity, and quality of information, access points, and the way libraries support organizations. Moreover, agricultural research has become multidisciplinary, embracing the fields of biophysics and the social sciences, so that no single library can provide information as expected by scientists. This paper traces teh development of the CoP of the Consultative Group on International Agricultural Research (CGIAR) information managemnet professionals (IMPs) and discusses the issues, challenges, constraints, activities and future plans.